Investigations on Mechanical Behavior of Al6061-TiO2-SiC Produced by Stir Casting - N, Nagendran; V K, Shanmuganathan; N, Gayathri; K, Suresh; S, Aravindh; E, Prakash (International Journal of Engineering and Technology, 2018)
Fine mechanical and thermal properties of metal matrix composites make them more demanding in various fields such as automotive, aerospace and structural applications. In this paper an effort has been made to fabricate a metal matrix composite, Titanium-di-oxide and silicon carbide reinforced in Al 6061 matrix using stir casting method. The reinforcements were added in 2%, 4% and 6% of weight to Al6061 to fabricate the metal matrix composite. Castings were machined and the specimens were prepared for various testing. Mechanical properties such as tensile strength, hardness, and corrosion analysis were studied for various compositions of reinforcements. And then the reinforcement was analyzed and studied for the improvement of mechanical properties in the material.Â Â